Distance Education to Improve the Quality of Asthma Treatment in Primary Health Care - Rudi Roman; Karine Margarites Lima; Maria Angela Fontoura Moreira; Roberto Nunes Umpierre; Lisiane Hauser; Dimitris V Rados; Alvaro Vigo; Marcelo Rodrigues Gonçalves; Sotero Serrate Mengue; Erno Harzheim (Sociedade Brasileira de Medicina de Família e Comunidade, 2019)
Objective: The mere dissemination of standard care recommendations has been insufficient to improve clinical results in patients with asthma. The objective of the present study was to evaluate the clinical effectiveness of a multifaceted asthma distance education for primary care providers. Methods: Cluster randomized controlled trial. Full primary care teams were included if they had access to telehealth support and free basic asthma treatment. Before randomization, selected teams indicated asthma patients between 5-45 years old for inclusion. The intervention group received three interactive online sessions, printed educational material, reminders, booklet for patients, and frequent stimulus to use consulting services. The control group received no intervention. Symptomfree days per two weeks was the primary result. Controlled asthma, unscheduled asthma doctor visits, and preventive inhaled corticosteroid use were the secondary results. Six months after intervention, the results were compared with baseline data using generalized estimating equations for repeated measures and clustering effect. Results: Were enrolled 71 primary care teams and 443 individuals. Most patients (60.3%) were female, and 44% were younger than 12 years old. The attendance of interactive sessions by the teams was 50%. The odds ratio (OR) for additional symptom-free day was 1.31 (95%CI 0.61-2.82; p=0.49). For the secondary results, the results were: controlled asthma OR 1.29 (95%CI 0.89-1.87; p=0.18); unscheduled asthma doctor visits OR 0.81 (95%CI 0.60-1.10; p=0.17); and preventive inhaled corticosteroid use OR 1.02 (95%CI 0.71-1.47; p=0.91). Conclusions: Multifaceted distance education in asthma care for primary care providers was not effective to improve patients' results. Telemedicine needs to deal with significant obstacles in professional education. ClinicalTrials.gov registry: NCT01595971.